El proceso de fraseologización de la locución adverbial española en un abrir y cerrar de ojos - Pascual-López, Xavier (Studia Romanica Posnaniensia, 2025)
This article explores the diachronic phraseologization process of the Spanish adverbial idiom en un abrir y cerrar de ojos (meaning “in an instant” or “very quickly”). Taking as a starting point its first known formulation in Ancient Greek (ἐν ῥιπῇ ὀφθαλμοῦ) and its Latin rendering (in ictu oculi), the study examines how Spanish develops its own distinct path of evolution. Through the analysis of historical corpora and lexicographic records, the article traces the idiom’s internal variation and gradual consolidation into its modern fixed form. Special attention is given to the syntactic and lexical shifts that signal the stages of lexicalization, grammaticalization, and institutionalization. Comparative references to other languages, as well as competing Spanish variants, provide a broader cross-linguistic context. The study contributes to historical phraseology by highlighting how fixed expressions emerge, stabilize and consolidate over time within linguistic systems.